Tailor made CuO/ZIF-8 hybrid structure as a potential candidate for thermocatalytic degradation of nitrocellulose - Zhao, Ningning; Yu, Zhong; Wang, Jia; Ma, Haixia; Yao, Ergang; An, Ting; Zhao, Fengqi; Yu, Xiaojiao (Thermochimica acta, 2022)
•Catalytic effects of CuO/ZIF-8 on the thermolysis process of NC are first studied.•Pyrolysis behavior and kinetics of NC/catalyst complex were evaluated comparatively.•Catalytic activity of CuO/ZIF-8 is confirmed to be superior to that of CuO and ZIF-8. CuO/ZIF-8 hybrid structure was obtained by adding the PVP-modified foliaceous CuO microstructures during the preparation of ZIF-8 polygon particles as a promising candidate for promoting the thermolysis process of NC. Thermoanalysis and pyrolysis kinetics based on the DSC and TG/DTG data revealed that the CuO/ZIF-8-NC decomposition had a weightlessness rate of 77.81%, heat release of 2882.5 J⋅g–1, the exothermic peak temperature of 471.25 K, and activation energy of 172.2 ± 16.0 kJ⋅mol–1, indicating that CuO/ZIF-8 has better catalytic activity than CuO and ZIF-8. The reconstructed nth-order kinetic models for NC/catalysis complexes were obtained using a modified fitting algorithm based on the results of isoconversional kinetic analysis, indicating that CuO/ZIF-8, CuO, and ZIF-8 had different catalytic effects on the thermolysis pathways of NC. This study suggests that CuO/ZIF-8 composite may have prospective application as a high potential and unique catalyst for accelerating NC pyrolysis. [Display omitted]